Quality of life in surgically reconstructed incorporated congenital heart disease to cardiac rehabilitation. Thirteen years experience - Francisco Carballés García; Winda Rodríguez; Samuel A. González Goyri; Eutivides Aguilera Sánchez; María T. Consuegra Chuairey (ECIMED, 2014)
Introduction and Objectives: Cardiovascular rehabilitation in patients with congenital heart defects reconstructed main purpose is to prolong survival in the best conditions posibles.En This article presents an analysis of the behavior of variables measuring the quality of life inthis type of heart disease was performed. Methods: Included in 2454 congenital heart disease surgically reconstructed in the period between 1992 and 2004, having joined the Cardiac Rehabilitation Program of the Child, the William Soler Pediatric Cardiology, from pre-surgical step, followed with postoperative scheduled checkups. Variables such as age, nutritional status, baseline functional capacity and exercise, the need for drug treatment and social development reached thirteen years of the program were studied. Results: Tetralogy of Fallot was the most common congenital heart disease (21.0%) operated. An average follow-up of 5 to 10 years after surgery was performed. At thirteen, the majority of patients were between 6 and 15 years of age, nutritional status assessment revealed that 80.3% were normal weight, 72.9% of patients remained free of symptoms and functional capacity improved with rehabilitation efforts, on the other hand only 15.5% remained on medication. 76.8% of patients were incorporated into the various levels of education. Conclusions: The quality of life of the reconstructed congenital heart disease patients improved significantly with infant cardiac rehabilitation.